Monetary and Macroprudential Policies in an Intangible Economy - Guido Baldi; André Bodmer (Credit and Capital Markets – Kredit und Kapital, 2020)
Advanced economies are increasingly based on intangible capital. Intangible capital has at least two special characteristics compared to tangible capital. First, it can be simultaneously used to produce different goods. Second, it is less suitable as collateral for obtaining external funds than tangible capital. These features could influence monetary and macroprudential policies. Against this backdrop, we study the effects of monetary and macroprudential policies by using a dynamic stochastic general equilibrium model with intangible capital and a banking sector. In our model, sector-speci c productivity shocks to tangible and intangible production have different effects on the economy, in particular on inflation and loans. In addition, the two shocks lead to different reactions of monetary and macroprudential policies. As a result, the volatility of macroeconomic variables differs across shocks and policy rules. In particular, augmented Taylor rules increase the volatility of loans after an intangible productivity shock and, from this perspective, appear to be less desirable than macroprudential rules after this type of shock. However, welfare effects of different policy rules are not qualitatively different across shocks because of similar impacts on the volatility of consumption.
Keywords: E22; E44; E52; 330; Intangible Capital; Macroprudential Policy; Monetary Policy